If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8s + 3 = 11 Reorder the terms: 3 + 8s = 11 Solving 3 + 8s = 11 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8s = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 8s = 11 + -3 8s = 11 + -3 Combine like terms: 11 + -3 = 8 8s = 8 Divide each side by '8'. s = 1 Simplifying s = 1
| solveV=lwh | | 21/2m=133/4 | | 4x-7+86=9x+4 | | 6j-5=4j-7 | | 2(x-6)=6(x+4) | | 6j+5=4j-7 | | -3(2x-4)=4(1.5x-3) | | -3(2x-4)=4((3/2x)-3) | | -70x+15=-23-18x | | -8/7-(-1/2) | | 2(15x-4)=8(3x+8) | | -1/9-(-2/15) | | -5.29-1.4d=-12.4d+12.3d+18.24 | | 6(x-2)=2x+7 | | 0.14y+0.09(y+7000)=2470 | | 5(x+10)=140 | | 3/4-(-1/9) | | X+8+3x+2=90 | | 5r+4=2r+46 | | 5x+0.3=20.3 | | f(-3)=9-4(-3)+6 | | x^3a+bx+c=0 | | 160=-9d+7 | | 1.32=x-0.2x | | a+bx+cx^3=c | | 2(-8)-15=6(-8)+17 | | -(p-3)=-3(1+p) | | -6(-6-6k)-3k=16+7k | | 19=9r-8 | | 15.6b+0.03=10.35+16.4b | | 35=9r-10 | | 7/10x=332 |